PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP STOCK RETURN PADA PERUSAHAAN YANG BERKAITAN DENGAN LINGKUNGAN YANG LISTING DI BURSA EFEK INDONESIA - Eman Sukanto; Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
"> This study examines the effect of independent variables are reporting corporate social responsibility ( CSR ) environmental dimensions , social, and economy, on the dependent variable of stock returns by partially or simultaneously. The study was conducted on 3 months period before and after the publication of the annual report in 2012 . The object of the research is a company listed on the Indonesian Stock Exchange and publish the annual report . Samples were taken as many as 50 companies , with a business group in the fields of Agriculture , Mining , Basic Industry and Chemicals , Miscellaneous Industry , and Consumer Goods . Data were tested with eviews program. Test results show the following : CSR partial test showed variable environmentis negatively affect to the stock return , positive effect on the CSR economy, and CSR social positively influence on stock return . The results of the simultaneous test of CSR environment , social , and economy , together influential on stock return . This shows that the company is already implementing the overall dimensions of CSR ( environment , economy , and social ) will increase the company’s stock return visits of cummulative Abnormal Return indicator .